Innovation studies, social innovation, and sustainability transitions research: From mutual ignorance towards an integrative perspective? - Attila Havas; Doris Schartinger; Karl Matthias Weber (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
Goal-oriented transformative change processes - that is, system-transforming processes that are guided by the ambition to resolve current or expected future societal challenges of various kinds - can only start once possible goals are considered by key stakeholders and the relevant actors are committed to act. Hence, there is a need for widening the scope of the current, partial conceptual models to consider the co-evolutionary interactions between technology, economy, and society to understand these changes. This claim is based on our review of Innovation Studies, Social Innovation research, and Sustainability Transitions research. The paper discusses the key conceptual elements of each strand; offers a definition of goal-oriented transformative change and building blocks for a new, integrative framework to analyse it; proposes directions for future research and draw tentative governance and policy implications.
Keywords: B52; H12; L31; O30; O31; O33; O35; O38; O44; P11; Q01; Q50; Q54; Q55; Q58; 330; Innovation studies; Social innovation research; Sustainability transitions research; Focussed literature review; Goal-oriented transformative change; A new integrative analytical framework